Route to chaos and bifurcation analysis in a multi-cell DC/DC buck converter, modelling and simulation. (2016) - Koubaâ, Karama
This paper investigates the route to chaos in a multi-cell DC/DC buck converter controlled using a proportional controller. Nonlinear phenomena and discontinuities, inherent in this type of converters, yield to border collision bifurcation, due essentially to a structural change in the system after hitting a boundary. In this work, we focus on the degenerate flip bifurcation, characterised by degenerated cycles of double period when crossing the boundary and leading directly to robust chaos in cyclical sets. The distinctive feature in this study lies in the use of a simplified discrete model of the converter and the analysis of the route to chaos by the search of fixed points with their domains of stability and the appeal of the Feigin method to predict the route to chaos. The four-cell converter is treated in simulation to confirm the theoretical results.